Composite Materials: Surface‐Modified Porous Carbon Nitride Composites as Highly Efficient Electrocatalyst for Zn‐Air Batteries (Adv. Energy Mater. 1/2018). Issue 1 (5th January 2018) - Niu, Wenhan; Li, Zhao; Marcus, Kyle; Zhou, Le; Li, Yilun; Ye, Ruquan; Liang, Kun; Yang, Yang
Abstract : A rationally designed CoSx ‐C3 N4 ‐graphene composite displays excellent activity and stability toward oxygen evolution and reduction reactions, surpassing electrocatalytic performance shown by the state‐of‐the‐art precious metal catalysts for Zn‐air batteries. The remarkable performance of the developed air‐electrode is attributed to the internally accessible electrochemical active sites and the facilitated transport of intermediates in the porous structure. This is reported by Yang Yang and co‐workers in article number1701642 .